STRATEGI HUBUNGAN INDONESIA DENGAN MALAYSIA DALAM MEWUJUDKAN DRUG FREE ASEAN 2015 - Istiqomah, Ratih Nur; Hanura, Marten; Susiatiningsih, Hermini (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Drugs trafficking is one of the most salient transnational crimes threateningASEAN member states especially Indonesia and Malaysia. The bilateralcooperation between both countries against transnational drugs trafficking isone of the efforts in combating drug issues happening in those countries.However, the implementation of the cooperation has not effectively reduced thedrugs problem between Indonesia and Malaysia particularly in the years of2009/2010 and 2013/2014. This research aims to observe the strategyestablished by Indonesia and Malaysia in combating drugs offences under thescheme of Drug-Free ASEAN 2015, using the theory of sociological liberalismand SWOT. Indonesia and Malaysia in combating drugs offences under thescheme of Drug-Free ASEAN 2015, using the theory of sociological liberalismand SWOT. The study employs qualitative method with descriptive-analysisand research techniques of literature reviews and interviews. This researchfound numerous factors undermining the effectiveness of the cooperationbetween Indonesia and Malaysia such as social, economy, politics, law, andworking mechanism. This paper offers a number of strategic recommendationsto enhance Indonesia and Malaysia’s cooperation in tackling their drugsproblems.